MODELING OF PROCESS OF DECISION-MAKING BY PARTICIPANTS OF INFORMAL VENTURE MARKET - Ekaterina I. Bragina (Статистика и экономика)
A new approach for the evaluation of innovative projects by business angels, based on the concept of building color-graphic cards with further it’s processing by neural networks is proposed in this article. The most important criteria for evaluation of innovative projects in the deal flow and due diligence stages selected. Each criterion is supposed to be evaluated by six components, giving a complete picture of the extent of its study. The criteria, as well as its components, are ranked in order of importance for a business angel. A method of processing building color-graphic cards by neural network is also proposed in this work.